Effect of Free‐Stream Turbulence on the Power Performance and Wake Characteristics of Paired Counter‐Rotating Vertical‐Axis Wind Turbines - Ayoub Talamalek; Mark C. Runacres; Tim De Troyer (Wind Energy)
ABSTRACT Vertical‐axis wind turbines (VAWTs) operate in the atmospheric boundary layer and are frequently subjected to turbulent flow. The objective of this study is to investigate the effect of free‐stream turbulence on the power performance and wake characteristics of a pair of counter‐rotating VAWTs. The research was conducted using wind tunnel experiments, which involved testing an isolated VAWT and two configurations of paired VAWTs with different rotational direction combinations. The experiments were conducted under two different turbulence intensities, 0.39% and 6.7%, with the latter being achieved by placing a passive wooden grid in the wind tunnel. The mechanical power output of the turbines was measured through torque and angular speed sensors, and the wake up to six rotor diameters downstream of paired VAWTs was characterised using constant temperature anemometry. The results show that when the turbulence intensity increases, the power coefficient of the isolated VAWT increases by 11%, while paired VAWTs experience an increase of up to 15%. Additionally, it is shown that the impact of increased free‐stream turbulence on the evolution and recovery of the wake is minimal, leading to only a slight reduction in the velocity deficit.